2007
DOI: 10.1038/sj.bjp.0707243
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H3‐receptor agonists and imidazole‐based H3‐receptor antagonists can be thermodynamically discriminated

Abstract: Background and purpose: Studies suggest that measurement of thermodynamic parameters can allow discrimination of agonists and antagonists. Here we investigate whether agonists and antagonists can be thermodynamically discriminated at histamine H 3 receptors. 0 values for agonists remained unchanged or decreased with decreasing temperature, while antagonist pK I values increased with decreasing temperature; agonist binding was entropy-driven while antagonist binding was enthalpy and entropy-driven. In buffer A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
9
2
Order By: Relevance
“…Weiland et al (1979) were the first to find that antagonists and agonists can be thermodynamically discriminated at the ␤-adrenergic receptor. Subsequently, several radioligand binding studies at the cholecystokinin CCK 2 receptor (Harper et al, 2007b), ␤-adrenergic receptor (Weiland et al, 1979;Contreras et al, 1986a,b), serotonin 5-HT 1A -receptor , histamine H 3 receptor (Harper et al, 2007a), dopamine D 2 receptor (Kilpatrick et al, 1986;Duarte et al, 1988) and adenosine A 1 and A 2A receptors were performed at different temperatures to determine thermodynamic parameters such as binding enthalpy (⌬H°) and binding entropy (⌬S°) of the ligand to the receptor. These studies showed that a thermodynamic discrimination between agonism and antagonism is only possible at some of the receptors (e.g., ␤-adrenergic receptor, 5-HT 3 , A 1 , and A 2A receptors).…”
mentioning
confidence: 99%
“…Weiland et al (1979) were the first to find that antagonists and agonists can be thermodynamically discriminated at the ␤-adrenergic receptor. Subsequently, several radioligand binding studies at the cholecystokinin CCK 2 receptor (Harper et al, 2007b), ␤-adrenergic receptor (Weiland et al, 1979;Contreras et al, 1986a,b), serotonin 5-HT 1A -receptor , histamine H 3 receptor (Harper et al, 2007a), dopamine D 2 receptor (Kilpatrick et al, 1986;Duarte et al, 1988) and adenosine A 1 and A 2A receptors were performed at different temperatures to determine thermodynamic parameters such as binding enthalpy (⌬H°) and binding entropy (⌬S°) of the ligand to the receptor. These studies showed that a thermodynamic discrimination between agonism and antagonism is only possible at some of the receptors (e.g., ␤-adrenergic receptor, 5-HT 3 , A 1 , and A 2A receptors).…”
mentioning
confidence: 99%
“…Moreover, a temperature dependent measurement of rate constants followed by the calculation of the Gibbs energy of activation, leads to the enthalpy and entropy of activation by the same machinery as in pure thermodynamics. For example, at the guinea-pig histamine H 3 receptor, the rate constants for association and dissociation of [ 3 H]clobenpropit was determined in dependence of temperature [14]. Based on these rate constants, the Gibbs energy, enthalpy and entropy of activation for the association process can be calculated ( Figure 3, Table 2).…”
Section: From Binding Kinetics To Thermodynamic Quantitiesmentioning
confidence: 99%
“…Based on these rate constants, the Gibbs energy, enthalpy and entropy of activation for the association process can be calculated ( Figure 3, Table 2). Taking into account the experimental errors based on the data in literature [14], the entropy term of activation is zero. Thus, the reaction rates of association and dissociation are only determined by enthalpy (Table 2).…”
Section: From Binding Kinetics To Thermodynamic Quantitiesmentioning
confidence: 99%
See 2 more Smart Citations